Pengaruh Motivasi, Komunikasi, dan Stres Kerja terhadap Kepuasan Kerja Karyawan di Kantor Bappeda Kota Solok - Visky Iksa Novandra; Ida Nirwana; Nurhayati Nurhayati (BADAN PENERBIT STIEPARI PRESS, 2025)
This research seeks to determine: (1) The impact of motivation on employee job satisfaction at the Solok City BAPPEDA Office; (2) the influence of communication on employee job satisfaction at the Solok City BAPPEDA Office; (3) the effect of work stress on employee job satisfaction at the Solok City BAPPEDA Office; (4) the combined effects of motivation, communication, and work stress on employee job satisfaction at the Solok City BAPPEDA Office. The study was conducted at the Solok City BAPPEDA Office using primary data. Total sampling was used as the sampling method, with questionnaires distributed to gather data. The findings revealed that: (1) Motivation positively influenced employee job satisfaction at the Solok City BAPPEDA Office, as indicated by a tcal value of 2.737, which is higher than the ttable at a 5% significance level, specifically 2.01537, thus 2.737 > 2.01537, along with a significant probability value of (0.009 < 0.05); (2) Communication had an impact on employee job satisfaction at the Solok City BAPPEDA Office, shown by a tcal value of 2.098 being greater than the ttable at a 5% significance level, which is 2.01537, so 2.098 > 2.01537, and a significant probability value of (0.042 < 0.05); (3) Work stress was shown to affect employee job satisfaction at the Solok City BAPPEDA Office, with a tcal value of 3.503 exceeding the ttable at a 5% significance level, which is 2.01537, meaning 3.503 > 2.01537 and a significant probability value of (0.001 < 0.05); (4) Collectively, motivation, communication, and work stress significantly influenced employee job satisfaction at the Solok City BAPPEDA Office, with an R square of 0.682, indicating 68.2%, with the remaining 31.8% influenced by other factors.